The First University Lying-In Hospital: Göttingen in the History of Man-Midwifery - Schlumbohm, Jürgen (Historical Studies on Central Europe, 2022)
In France, the Netherlands, and Great Britain, male medical doctors and surgeons were turning to midwifery earlier than their German counterparts. Equally, in France and in England, maternity wards and hospitals emerged earlier than in Germany. Nevertheless, the lying-in hospital of Göttingen, founded in 1751, played a pioneering role: it was the first university institution in the world. Its main purpose was to give practical, hands-on education in obstetrics to medical students. The first professor of obstetrics and director of Göttingen University lying-in hospital, Johann Georg Roederer (1726–1763), was willing to transform the traditional female craft of midwifery into a branch of medical science. Through educating the next generation of obstetricians and his scholarly publications, he had a major impact in Germany and beyond. For the period around 1800, an exceptionally rich collection of printed and archival sources allows deep insight into the practices of Göttingen University’s lying-in hospital. The roles of the director, the midwife, the students, and the patients can be studied in detail, and compared to lying-in hospitals in other countries. Special attention is given to the practice of practical education. Finally, the success of the maternity hospital can be assessed, both in terms of the directors’ reputation, and the survival chances of mothers and children.